A new approach of indirect enzyme-linked immunosorbent assay for determination of D-glutamic acid through in situ conjugation. Issue 3 (3rd May 2016) - Sakamoto, Seiichi; Nagamitsu, Rika; Matsuura, Yurino; Tsuneura, Yumi; Kurose, Hitoshi; Tanaka, Hiroyuki; Morimoto, Satoshi
Abstract : We propose a new approach of an indirect enzyme-linked immunosorbent assay (ELISA) for determination of D-glutamic acid (D-Glu) using a monoclonal antibody against D-glutamic acid (D-Glu-MAb), which recognizes D-Glu-glutaraldehyde (GA) molecule but not D-Glu molecule. Human serum albumin (HSA) was coated on an immunoplate and reacted with D-Glu via GA to produce D-Glu-GA-HSA conjugates in situ in the well to be recognized by D-Glu-MAb, which enabled the development of an indirect ELISA for the determination of free D-Glu. In this indirect ELISA, D-Glu can be specifically detected with limit of detection of 7.81μ g/mL. Since anti-conjugate antibodies are often produced, even though anti-hapten antibodies are desired, this new approach could be very useful as an application of anti-conjugate antibodies to the development of quantitative analysis for detecting hapten.